Mineralogical and geochemical evidence of magma mingling/mixing in the Sierra de las Cruces volcanic range, Mexican Volcanic Belt - Velasco-Tapia, F.; Rodríguez-Saavedra, P.; Márquez, A.; Navarro de León, I.; De Ignacio, C.; Marroquín Guerra, S. G.; Quintanilla-Garza, J.; Rangel-Álvarez, O.M. (Journal of Iberian Geology, 2013)
Pliocene – Pleistocene lava flows, mainly of dacitic composition, are exposed in the Sierra de las Cruces (SC) volcanic range within the Mexican Volcanic Belt (MVB). SC volcanic rocks are porphyritic, generally containing an assemblage of plagioclase + amphibole + orthopyroxene ± clinopyroxene ± quartz ± Fe-Ti oxides. Most of them exhibit diverse mineralogical and geochemical features that attest a magma mixing and mingling processes with concomitant fractional crystallization in which a small volume of hot andesite magma injects into dacitic magma. Both rock types are probably derived from partial melting of continental crust at different levels. The evidences of magma mixing and mingling include: (a) normal and sieved plagioclases in the same sample, rounded and embayed crystals, and armoured rims over the dissolved crystal surfaces; (b) subrounded, vesicular magmatic enclaves, ranging from a few millimeters to ~20 centimeters in size, with plagioclase + orthopyroxene + amphibole + quartz ± olivine ± Fe-Ti-oxides assemblage; (c) mineral chemistry evidence such as crystals with reaction rims or heterogeneous plagioclase compositions (inverse and oscillatory zoning or normally and inversely zoned crystals) in the same sample; and (d) elemental geochemical variations and trace-element ratio more akin to magma mixing and to some extent diffusion process. These andesitic enclaves could be considered as portions of the intermediate magma that did not mix completely (mingling) with the felsic host lavas, confirming the major role of magma mixing and mingling processes in the overall evolution of the MVB